Obliterated Firearms Markings Documented in an African Country - Henwood, Bailey J. (Cranfield University, 2023)
For the first time, a 'boots on the ground' approach has been taken to understand obliterations made to Small Arms and Light Weapons (SALW) recovered and documented in an African state, Country X. 126 firearms, primarily AK-pattern, were documented by Conflict Armament Research during a 10-year mission. These weapons were sanitised by local actors by removing identifying markings such as serial numbers and factory marks. Each obliteration was carefully analysed to determine the type of tool used by identifying the class characteristics of the toolmark, and to identify precisely which marks were removed. An obliteration code system has been developed, which identifies the tool type, completeness, marks removed, directionality, and any additional concealment. These codes have allowed to development of a database of obliterations and will, in turn, aid the intelligence-led investigation into the local forensic awareness, physical capabilities, and the motivation to obscure the SALWs identity. The results indicate that many of the weapons in each profile were likely sanitised by the same node-or were at least under the instruction of one common actor. This study also established that the forensic awareness within Country X is relatively low, as many of these marks may be recoverable using either traditional or novel means, if given the opportunity. The motivation for many of these weapons lies in the maintenance of monetary value, while concealing the identity to evade tracing efforts. This paper utilises a novel approach to understand weapon sanitisation in Country X, and how methods of obliteration can enhance further investigations in the region.
Keywords: Firearms; Diversion; Tracing; Intelligence; Sanitisation; Forensic Awareness; DSDS22; DSDS22 Paper Presentation